2018
DOI: 10.2147/clep.s155601
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime risks, loss of life expectancy, and health care expenditures for 19 types of cancer in Taiwan

Abstract: BackgroundThe mortality rates for different cancers are no longer an efficient tool for making national policy. The purpose of this study were to quantify the lifetime risks, life expectancies (LEs) after diagnosis, expected years of life lost (EYLL), and lifetime health care expenditures for 19 major cancers in Taiwan.MethodsA total of 831,314 patients with 19 pathologically proven cancers were abstracted from the Taiwan Cancer Registry from 1998 to 2012. They were linked to the National Mortality Registry (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…Another relevant indicator of societal burden is the lifetime spending for healthcare services of cancer, as summarized in Table 4. Lifetime cost for unknown staging of esophageal cancer in Taiwan male patients was US$ 30,778, which seems to be consistent with that (US$ 25,900) reported by Wu TY et al 19 . In the typical studies of cost-effectiveness, researcher hope to quantify the incremental cost-effectiveness ratio (ICER), which is an overall measure representing the economic value of an intervention, compared with an alternative (comparator) 31 .…”
Section: Indicators Of Societal Burdens: Expected Years Of Life Loss supporting
confidence: 89%
See 3 more Smart Citations
“…Another relevant indicator of societal burden is the lifetime spending for healthcare services of cancer, as summarized in Table 4. Lifetime cost for unknown staging of esophageal cancer in Taiwan male patients was US$ 30,778, which seems to be consistent with that (US$ 25,900) reported by Wu TY et al 19 . In the typical studies of cost-effectiveness, researcher hope to quantify the incremental cost-effectiveness ratio (ICER), which is an overall measure representing the economic value of an intervention, compared with an alternative (comparator) 31 .…”
Section: Indicators Of Societal Burdens: Expected Years Of Life Loss supporting
confidence: 89%
“…1). The LE of esophageal cancer without staging information in Taiwan (1998~2012) was 3.1 years, as reported by Wu TY et al 19 , indicating very limited or no improvement in prognosis. Regarding the prognosis of different pathological types, we found that the loss-of-LE of patients with adenocarcinoma was significantly lower than that of squamous cell carcinoma, which corroborate with previous reports 20,21 .…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Gallbladder cancer, as a highly lethal neoplasm, features late diagnosis, unsatisfactory treatment, and unfavorable prognosis with conventional therapy . Thus, it is critical and urgent to determine novel prognostic biomarkers and to discover the underlying mechanisms of GBC progression, thereby identifying targeted therapeutics for GBC.…”
Section: Introductionmentioning
confidence: 99%